Condensed Tannins in White Clover (Trifolium repens) Foliar Tissues Expressing the Transcription Factor TaMYB14-1 Bind to Forage Protein and Reduce Ammonia and Methane Emissions in vitro - Roldan, Marissa B.; Cousins, Greig; Muetzel, Stefan; Zeller, Wayne E.; Fraser, Karl; Salminen, Juha-Pekka; Blanc, Alexia; Kaur, Rupinder; Richardson, Kim; Maher, Dorothy; Jahufer, Zulfi; Woodfield, Derek R.; et al. (Frontiers in Plant Science, 2022)
Grazing ruminants contribute to global climate change through enteric methane and nitrous oxide emissions. However, animal consumption of the plant polyphenolics, proanthocyanidins, or condensed tannins (CTs) can decrease both methane emissions and urine nitrogen levels, leading to reduced nitrous oxide emissions, and concomitantly increase animal health and production. CTs are largely absent in the foliage of important temperate pasture legumes, such as white clover (Trifolium repens), but found in flowers and seed coats. Attempts at enhancing levels of CT expression in white clover leaves by mutagenesis and breeding have not been successful. However, the transformation of white clover with the TaMYB14-1 transcription factor from Trifolium arvense has resulted in the production of CTs in leaves up to 1.2% of dry matter (DM). In this study, two generations of breeding elevated foliar CTs to >2% of DM. The CTs consisted predominantly of prodelphinidins (PD, 75–93%) and procyanidins (PC, 17–25%) and had a mean degree of polymerization (mDP) of approximately 10 flavan-3-ol subunits. In vitro studies showed that foliar CTs were bound to bovine serum albumin and white clover proteins at pH 6.5 and were released at pH 2.-2.5. Using rumen in vitro assays, white clover leaves containing soluble CTs of 1.6–2.4% of DM significantly reduced methane production by 19% (p ≤0.01) and ammonia production by 60% (p ≤ 0.01) relative to non-transformed wild type (WT) controls after 6 h of incubation. These results provide valuable information for further studies using CT expressing white clover leaves for bloat prevention and reduced greenhouse gas emissions in vivo.